Jezik, religija i osobna iskustva u Buberovu Ja-Ti odnosu. - Skelac, Ines (Nova Prisutnost, 2025)
This paper explores Buber's concept of the I-Thou relationship by analyzing details from his life and philosophy that influenced the formation of this relationship, including his mother's abandonment during his early childhood, exposure to various languages, and religious perspectives. Mother's departure deeply imprints Buber's perception of security and authenticity in interpersonal relationships. At the same time, multilingualism contributed to his specific approach to language as a medium of communication, which is often insufficient for establishing a true relationship with the Other. Buber emphasized the importance of a direct, personal encounter with God, which is reflected in encounters with people and nature. In this context, the paper also examines Buber's relationship with animals, which he perceived as beings with whom an I-Thou relationship could be established. In conclusion, the paper demonstrates that Buber's I-Thou relationship is not primarily verbal, but encompasses all aspects of human existence, from the unconscious and non-verbal to the religious and existential.